2002
DOI: 10.1001/archinte.162.16.1842
|View full text |Cite
|
Sign up to set email alerts
|

Influenza Burden of Illness

Abstract: These results confirm the substantial burden of illness of influenza. The results should be useful for evaluating the cost-effectiveness of strategies against influenza.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
35
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(41 citation statements)
references
References 29 publications
5
35
1
Order By: Relevance
“…The mean number of work days lost because of influenza in our study was similar to that reported from other countries such as France, Finland, Italy, Japan, and the United States 11, 27, 28, 29, 30. Our results were in keeping with various studies that suggest that indirect costs comprise the bulk of the economic burden associated with influenza illness in middle‐ and high‐income countries 5, 31, 32.…”
Section: Discussionsupporting
confidence: 91%
“…The mean number of work days lost because of influenza in our study was similar to that reported from other countries such as France, Finland, Italy, Japan, and the United States 11, 27, 28, 29, 30. Our results were in keeping with various studies that suggest that indirect costs comprise the bulk of the economic burden associated with influenza illness in middle‐ and high‐income countries 5, 31, 32.…”
Section: Discussionsupporting
confidence: 91%
“…OECD statistics on employment rates were used, representing the population of working age (15–64 years). The expected number of days taken off work for adults in this study was estimated as the product of the probability of taking time off (91% for sickness from influenza), [42] and the average duration of time off for influenza sickness, 4 days [42, 43]. This was applied to all countries and for all adult target groups.…”
Section: Methodsmentioning
confidence: 99%
“…The interpandemic influenza SAR values in the literature vary widely, with some values in the 0.13-0.15 range, and others at 0.38 (Carrat et al, 2002) (which drops to 0.362 after accounting for coinfections Ferguson et al, 2005) and even higher (Carrat et al, 2002). Although the degree of population immunity plays a role in the SAR, one of the main reasons for this heterogeneity is the differences in how a case is defined: the higher values include low-grade illnesses (e.g., with no fever) and do not obtain lab confirmation of influenza (Carrat et al, 2002), and the lower numbers require severe symptoms that do not include more than one-third of the lab-confirmed cases. Hence, our SAR is near the lower end of the empirical range, which is also consistent with our assumption that all infecteds withdraw to the bedroom (i.e., have severe symptoms).…”
Section: Interpandemic Influenzamentioning
confidence: 99%